Improving Health Care for Critically Ill Patients Using an Evidence‐Based Collaborative Approach to ABCDEF Bundle Dissemination and Implementation. Issue 3 (5th May 2018) - Barnes‐Daly, Mary Ann; Pun, Brenda T.; Harmon, Lori A.; Byrum, Diane G.; Kumar, Vishakha K.; Devlin, John W.; Stollings, Joanna L.; Puntillo, Kathleen A.; Engel, Heidi J.; Posa, Patricia J.; Barr, Juliana; Schweickert, William D.; et al.
ABSTRACT: Background: Patients admitted to intensive care units (ICUs) often experience pain, oversedation, prolonged mechanical ventilation, delirium, and weakness. These conditions are important in that they often lead to protracted physical, neurocognitive, and mental health sequelae now termed postintensive care syndrome. Changing current ICU practice will not only require the adoption of evidence‐based interventions but the development of effective and reliable teams to support these new practices. Objectives: To build on the success of bundled care and bridge an ongoing evidence‐practice gap, the Society of Critical Care Medicine (SCCM) recently launched the ICU Liberation ABCDEF Bundle Improvement Collaborative. The Collaborative aimed to foster the bedside application of the SCCM's Pain, Agitation, and Delirium Guidelines via the ABCDEF bundle. The purpose of this paper is to describe the history of the Collaborative, the evidence‐based implementation strategies used to foster change and teamwork, and the performance and outcome metrics used to monitor progress. Methods: Collaborative participants were required to attend four in‐person meetings, monthly colearning calls, database training sessions, an e‐Community listserv, and select in‐person site visits. Teams submitted patient‐level data and completed pre‐ and postimplementation questionnaires focused on the assessment of teamwork and collaboration, work environment, and overall ICU care. Faculty shared the evidence used to derive each bundle element as well as team‐based implementation strategies for improvement and sustainment. Results: Retention in the Collaborative was high, with 67 of 69 adult and eight of nine pediatric ICUs fully completing the program. Baseline and prospective data were collected on over 17, 000 critically ill patients. A variety of evidence‐based professional behavioral change interventions and novel implementation techniques were utilized and shared among Collaborative members. Linking Evidence to Action: Hospitals and health systems can use the Collaborative structure, strategies, and tools described in this paper to help successfully implement the ABCDEF bundle in their ICUs.